P250 A national study of non-invasive ventilation and clinical outcomes in cystic fibrosis. (15th November 2017) - Archangelidi, O; Simmonds, NJ; Carr, SB; Cullinan, P
Abstract : Introduction/Objectives: Non-invasive ventilation (NIV) is often used as a 'bridge' to transplantation, for symptom control or as an adjunct to physiotherapy. Whether or not NIV is being appropriately used in UK patients with CF, successfully targeting those who will benefit most, is unknown; nor is there information on the life expectancy of those who start on NIV. Methods: The present study is part of the CF-Epidemiological Network (CF-EpiNet project) and uses data from the UK Cystic Fibrosis Registry to describe the patterns of NIV use by patients in the UK. We examined the records of 11 120 patients and assembled a longitudinal, retrospective cohort from those seen between 2007 and 2015. We used Cox proportional hazard models to assess the survival of patients on NIV. Results: 1077 patients (715 adults and 362 children<16 years) had reported use of NIV recorded at least once. Usage increased after 2012 (figure 1 ). At the first recorded use of NIV the median (IQR) age was 21 years (14, 28), BMI 18.4 kg/m 2 (16.8, 22.7), 49.2% were male, 90.3% on PERT, 75.1% growing Pseudomonas, 54.6% homozygous F508del; the mean FVCpp was 64.5% and FEV1 pp 47.2%. At this time 68.8% of patients had a FEV1 pp <60%; 52% were <40%, while in adults this percentage reached 61%. In children there was a higher proportion starting treatment with better lung function ie ≥60% (33.8%). The median survival of patients who start NIV is 3.47 years. The hazard ratio for NIV use was 3.90 (95% CI: 3.06–4.96). Conclusions: Not surprisingly, patients start NIV when their lung function is significantly impaired. Yet, increased proportions of people with FEV1 pp ≥40% on NIV were also identified. The higher lung function at the start of NIV for children may reflect that it is used for purposes other than a bridge to transplant in this group; the registry only collects a yes/no variable for NIV use and not the reason for use. Survival after initiation of NIV is poor; this is likely reflect that NIV is a marker of disease severity but further analysis will be needed to explore this.